2020
DOI: 10.11648/j.acm.20200905.12
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Machine Learning Algorithms for Predicting Crash Injury Severity in Yemen: Hospital Case Study

Abstract: This study focused on exploiting machine learning algorithms for classifying and predicting injury severity of vehicle crashes in Yemen. The primary objective is to assess the contribution of the leading causes of injury severity. The selected machine learning algorithms compared with traditional statistical methods. The filtrated second data collected within two months (August-October 2015) from the two main hospitals included 156 injured patients of vehicle crashes reported from 128 locations. The data class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Results indicated that the various used algorithms have different accuracy rate at different roadway type. Most importantly, their study showed that holidays affect the crash severity (Almannaa et al, 2023).Several works were conducted to model traffic crashes globally ( (Almamlook et al, 2019;Almannaa et al, 2023;Al-Mistarehi et al, 2022;Al-Moqri et al, 2020;Alrumaidhi & Rakha, 2022;Anderson & Hernandez, 2017;Azhar et al, 2022) Most of these studies used machine learning algorithms including K-nearest neighborhoods (KNN), support vector machine, adaptive boosting tree or other machine learning algorithms (Ahmed et al, 2021;Almamlook et al, 2019;Almannaa et al, 2023a;Al-Mistarehi et al, 2022;Al-Moqri et al, 2020). Researchers indicated that providing driver sociodemographic attributes may improve the model prediction ( (Almannaa et al, 2023;Jamal et al, 2021;R.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results indicated that the various used algorithms have different accuracy rate at different roadway type. Most importantly, their study showed that holidays affect the crash severity (Almannaa et al, 2023).Several works were conducted to model traffic crashes globally ( (Almamlook et al, 2019;Almannaa et al, 2023;Al-Mistarehi et al, 2022;Al-Moqri et al, 2020;Alrumaidhi & Rakha, 2022;Anderson & Hernandez, 2017;Azhar et al, 2022) Most of these studies used machine learning algorithms including K-nearest neighborhoods (KNN), support vector machine, adaptive boosting tree or other machine learning algorithms (Ahmed et al, 2021;Almamlook et al, 2019;Almannaa et al, 2023a;Al-Mistarehi et al, 2022;Al-Moqri et al, 2020). Researchers indicated that providing driver sociodemographic attributes may improve the model prediction ( (Almannaa et al, 2023;Jamal et al, 2021;R.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Classical machine learning (ML) algorithms (e.g., logistic regression, k-nearest-neighbors, support vector machines, decision tree, random forests, etc.) have been used to develop a prediction model of human injury degree ( Al-Moqri et al, 2020 ; Mansoor et al, 2020 ; Liu et al, 2022 ). At the same time, in order to further explore the interaction relationship between objective factors in traffic accidents and human injury response to improve the accuracy of prediction models, deep learning (DL) method with higher computational complexity (e.g., deep neural network, convolutional neural network, long short-term memory, recurrent neural network, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, combining modern data sources frequently produces complex data sets with a large number of dimensions that are difficult to model using traditional statistical techniques. Machine learning methods, on the other hand, are highly adaptable, require few or no prior assumptions about the data, and can handle missing values, noise, and outliers [ 27 ]. In the field of traffic safety research, machine learning techniques have received a lot of attention.…”
Section: Introductionmentioning
confidence: 99%